STRUGGLE FOR ACHIEVING HAPPINESS IN SOFIA COPPOLA'S MARIE ANTOINETTE MOVIE (2006): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - WARDANI, DESINTA PUSPA (2011)
The study is to reveal how the struggle for Achieving happiness of the major character influences his personality. The objective of the study is to analyze the movie based on the structural analysis and the individual psychological approach. In analysis, the writer uses qualitative method. The object of the study is Marie Antoinette released in 2006. The data sources consist of primary and secondary data source. The primary data source Marie Antoinette movie and the secondary data sources are the other sources related to the primary data such as the information about director's biography and websites. The method of the data collection are watching the movie, taking notes the important data, arranging the data based on category of elements of literature review, and the last is looking for the supporting data. The technique of data analysis is descriptive analysis. After analyzing the movie of Sofia Coppola's Marie Antoinette, the writer concluded that there are several aspects of individual psychological approach of the major character The aspects consist of fictional finalism, striving for superiority inferiority feeling, style of live, social interest, and creative power. Marie Antoinette has some struggle to achieving happiness. She become queen of France and become good wife for her husband Louis Auguste. The facts above show that the final goal of Marie Antoinette guides her to be more creative to catch her happiness.